The true true story of Raja the Gullible (and his mother) - Alameddine, Rabih (Grove Press, an imprint of Grove Atlantic, 2025)
In a tiny Beirut apartment, sixty-three-year-old Raja and his mother live side by side. A beloved high school philosophy teacher and "the neighborhood homosexual," Raja relishes books, meditative walks, order, and solitude. Zalfa, his octogenarian mother, views her son's desire for privacy as a personal affront. She demands to know every detail of Raja's work life and love life, boundaries be damned. When Raja receives an invite to an all-expenses-paid writing residency in America, the timing couldn't be better. It arrives on the heels of a series of personal and national disasters that have left Raja longing for peace and quiet away from his mother and the heartache of Lebanon. But what at first seems a stroke of good fortune soon leads Raja to recount and relive the very disasters and past betrayals he wishes to forget.--